Rate of spermatogenic cell apoptosis in the testis of domestic chicken (Gallus gallus domesticus) at different age groups. - Musa Zakariah; Geado Agishi; Esther Z. Musa; Josephine J. Dasa; Yagana B. Majama; Yagana A. Gazali; Mohammed A.A. Mahdy (Poultry Science)
In both normal and pathological conditions, excess spermatogenic cells in the testicular tissue are known to be removed by the mechanism of apoptosis. There are a few studies on spermatogenic cell apoptosis in avian species. Therefore, the purpose of this study was to evaluate the rate of spermatogenic cell apoptosis in three different age groups of the local domestic chicken (Gallus gallus domesticus). Samples were collected from the testes of domestic chicken at three different reproductive stages; pre-pubertal, pubertal, and adult. The samples were subjected to transmission electron microscopy (TEM) and flow cytometry evaluations. TEM results revealed the morphological characteristics of apoptotic cells which included irregular nuclear and plasma membranes in the early stages of apoptosis, nuclear membrane rupture, nuclear material condensation, and fragments of apoptotic bodies in the later stages of apoptosis. The flow cytometry results revealed a significant difference between the mean percentage of apoptotic spermatogenic cells for the three age groups (P < 0.05). Post hoc analysis revealed a significant difference in the adult age group relative to the pre-pubertal age group. However, there was no significant difference between apoptotic spermatogenic cells of the pre-pubertal and the pubertal, and between the pubertal and the adult age groups. In conclusion, the present study revealed a gradual increase in the rate of apoptotic spermatogenic cells in the testes of domestic chicken during the pre-pubertal, pubertal, and adult age groups.